Practical approaches to animal health issues on organic farms. (2nd January 2019) - Plate, Peter
Abstract : A summary of a workshop attended by 15 delegates at the BCVA congress on 19th October 2018. The workshop started with an overview of organic animal health standards and the organic market. In the EU animal health standards promote 'positive health' and preventive medicine, but treatments can be given without the animals losing their organic status. This is different in some other countries, especially the USA, and this is relevant when UK producers export produce. A misunderstanding of standards can lead to potential welfare problems, but correctly managed, organic standards promote high levels of welfare and health. Some examples of common health issues and their management within the organic system are given — mastitis, calf issues, Johne's control, trace element deficiencies and parasite control.